EFFECT OF MICROBUBBLES ON THE GROWTH OF MUSTARD PAK CHOI (Brassica rapa L.) IN WICK SYSTEM HYDROPONICS - Joko Prasetyo; Fiqi Ibrahim Saqroth; Yusuf Hendrawan (Fakultas Teknologi Pertanian Universitas Brawijaya, 2022)
Mustard pak choi (Brassica rapa L.) is one of the vegetable plants used in the research object. The wick system is a simple hydroponic method that uses a wick as a link between nutrients and the roots of the growing media. With a flat container, the hydroponic system wick will use an aerator to provide oxygen needs. The research purpose is expected to design a hydroponic wick system with the addition of microbubble treatment and to determine the effect of treatment duration and quantity of microbubble technology on the growth of mustard greens, namely the number of leaves, leaf area, wet plant weight, plant root length, and leaf greenness index. Microbubble technology is a device that produces or delivers air bubbles with a diameter of fewer than 200 micrometers in water and provides optimization of the rate and amount of oxygen transfer. Mustard Pak choi will be observed from the number of leaves, leaf area, wet plant weight, plant root length, and leaf greenness index and, compared with control plants, is expected to increase the productivity of mustard Pak choi. The method applied examines the relationship of systematic changes of the independent variables of one or more variables from the experimental group. Data processing used a completely randomized factorial design with five repetitions and two factorials. The first factor was microbubble treatment for 3, 6, and 9 hours, and the second used 1, 2, and 3 diffuser outputs and one without control treatment. The results showed that the effect of time and the number of microbubbles had no significant effect on plant morphology. Still, the application of dissolved oxygen to the microbubbles impacted the growth of mustard Pak choi compared to the control and treatment. The results showed that oxygen causes the breakdown of nutrients that are more easily absorbed and increases plant quality